2016
DOI: 10.1007/s00330-016-4445-9
|View full text |Cite
|
Sign up to set email alerts
|

Advanced-stage hepatocellular carcinoma with portal vein thrombosis: conventional versus drug-eluting beads transcatheter arterial chemoembolization

Abstract: Objectives Our study sought to compare the overall survival in patients with hepatocellular carcinoma (HCC) and portal venous thrombosis (PVT), treated with either conventional trans-arterial chemoembolization (cTACE) or drug-eluting beads (DEB) TACE. Methods This retrospective analysis included a total of 133 patients, treated without cross-over and compared head-to-head by means or propensity score weighting. Mortality was compared using survival analysis upon propensity score weighting. Adverse events and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 51 publications
2
43
0
Order By: Relevance
“…However, PV thrombosis does portend a poorer prognosis [24] . As anticipated post embolization syndrome is the most common side effect reported post TACE, while encephalopathy was found in approximately 5% of patients, and elevated liver function tests as high as 20% of cases [23] . In a comparison, c-TACE and drug eluting bead TACE had similar safety profiles and survival rates comparable to treatment with sorafenib [23] .…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…However, PV thrombosis does portend a poorer prognosis [24] . As anticipated post embolization syndrome is the most common side effect reported post TACE, while encephalopathy was found in approximately 5% of patients, and elevated liver function tests as high as 20% of cases [23] . In a comparison, c-TACE and drug eluting bead TACE had similar safety profiles and survival rates comparable to treatment with sorafenib [23] .…”
Section: Discussionmentioning
confidence: 61%
“…As anticipated post embolization syndrome is the most common side effect reported post TACE, while encephalopathy was found in approximately 5% of patients, and elevated liver function tests as high as 20% of cases [23] . In a comparison, c-TACE and drug eluting bead TACE had similar safety profiles and survival rates comparable to treatment with sorafenib [23] . The use of AFP as an oncologic marker of response to loco-regional therapy for HCC has been proven to be effective [25] .…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…revealed that there was no difference regarding the median OS in advanced HCC patients with portal vein thrombosis treated by DEB-TACE with LC bead ® and patients treated by cTACE. 16 However, a retrospective cohort study conducted by Rahman et al elucidateed that in unresectable HCC patients, DEB-TACE presented with a more prolonged median survival time compared with cTACE. 17 Furthermore, a meta-analysis demonstrated that the 1 year, 2 year and 3 year survival rates were elevated in HCC patients treated by DEB-TACE compared with cTACE, and the 1 year-as well as 2 year-relapse-free survival rates were also increased in patients treated with DEB-TACE.…”
Section: Discussionmentioning
confidence: 99%
“…Among 16 articles that retrospectively analyzed DEB‐TACE versus cTACE, five described the superiority of DEB‐TACE, three showed an advantage of cTACE, and the remaining eight showed equivalent effect or adverse events. Individual evaluation of objective response rate, TTP, OS, and adverse events, did not show definite advantages of DEB‐TACE over cTACE in these retrospective studies.…”
Section: Transcatheter Arterial Therapymentioning
confidence: 99%